Pengeringan Lapis Tipis Kopra Putih Menggunakan Oven Pengering: White Copra Thin Layer Method using Drying Oven - Murad Murad; Rahmat Sabani; Guyup Mahardhian Dwi Putra (Fakultas Teknologi Pangan & Agroindustri (Fatepa) Universitas Mataram dan Perhimpunan Teknik Pertanian (PERTETA), 2015)
West Nusa Tenggara has enormous potential as coconut producer in Indonesia. With total area 64.297,10 ha, it can produced coconuts in amount of 49670.93 tons (NTB in Figures, 2010). Most of the coconut was sent to Java Island, whereas some local communities process the coconuts into copra and traditional coconut oil. However, NTB as producer of copra has not been able to produce good quality copra because the traditional process is conducted using simple processing equipment, requires large human power, and long processing time. Due to these limitiation, it is necessary to implement appropriate technology by using shelf-type dryer (tray dryer) tool that utilizes solar energy as a source of thermal energy. Using solar collectors panel, the dryer produce heat higher than using direct drying and the temperature can be controlled. Purpose of this study was to determine characteristics of copra drying processes (temperature, relative humidity, effective drying rate, and relation between effective drying rate and water content) using oven as ideal drying tool, for further application on solar-energy tray-dryer type. Drying was conducted until water content achieved 9%, the observed and calculations data were plotted into graphic then studied descriptively. Calculated variables are reduction in weight material, moisture content, drying air temperature, ambient air temperature, outflow air temperature, material temperature, air humidity, drying efficiency, air flow rate, and intensity of solar radiation. Constant value indicates that the higher the drying air temperature, the more rapid time were needed to decrease moisture content of the material, therefore the obtained general equation for water content ratio becomes MR = exp (-0,0141.T - 0.2583) * t.